PENERAPAN METODE EKSPERIMEN UNTUK MENINGKATKAN AKTIVITAS BELAJAR SISWA DALAM PEMBELAJARAN ILMU PENGETAHUAN ALAM - (F34211128), Urbanus; ., Sukmawati; ., Zainuddin (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2013)
The problem that the background for this research study include the lack of activity in the fourth grade students of SDN 24 Kuala Pade. The purpose of this study were 1) To get an idea of ??the learning plan with an experimental method that can improve student learning activities in science teaching. 2) To get an overview of the implementation of learning with experimental methods in order to improve student learning activities in science teaching. 3) To determine the increased activity of the fourth grade students of SDN 24 Kuala Pade. This study uses classroom action research (Classroom Action Research), as many as three (3) cycles. Each cycle consists of four stages: action planning, action, observation, and reflection. Objectives of this study were Class IV students of SDN 24 Kuala Pade. Data obtained observation sheet teaching and learning activities and achievement test. Learning plan with the experimental method to study Natural Sciences 24 class IV SDN Kuala Pade Both categories have been implemented once. It can be seen on sheet 1 IPKG first cycle with an average score of 3.48, while IPKG 1 in the second cycle with a mean score of 3.72, and 1 in the third cycle IPKG with mean score 3.95. Implementation of learning with experiments on learning methods of Natural Science in Class IV SDN 24 Kuala Pade has implemented Good category once. It can be seen on the sheet IPKG 2 in cycle I to score an average of 3.55, while IPKG 2 in II with average score 3.93, and IPKG 2 in cycle III with average score 3.99. The use of experimental methods in learning Natural Science Learning activities were able to improve students' fourth grade Kuala Pade SDN 24. This can be seen in the observation sheet the average percentage of learners for physical activity from early observations (base line) obtained 13.88%, in the cycle I gained 71.93%, 83.3% earned cycle II and cycle III acquired 94.43%. Further to mental activity from early observations (base line) 8.33%, on cycle I obtained 44.29%, 63.86% obtained cycle II and cycle III acquired 83.3%. And subsequent emotional activity from early observations (base line) of 0%, the cycle I obtained 43.16%, 68.98% obtained cycle II and cycle III acquired 83.32%. Thus studies using experimental methods to enhance students' learning activity class IV SDN 24 Kuala Pade. Abstrak: Masalah yang melatar belakangi penelitian ini diantaranya adalah rendahnya aktivitas belajar peserta didik di kelas IV SDN 24 Kuala Pade. Tujuan dari penelitian ini adalah 1) Untuk mendapatkan gambaran perencanaan pembelajaran dengan metode eksperimen sehingga dapat meningkatkan aktivitas belajar siswa pada pembelajaran IPA. 2) Untuk mendapatkan gambaran tentang pelaksanaan pembelajaran dengan metode eksperimen agar dapat meningkatkan aktivitas belajar siswa pada pembelajaran IPA. 3) Untuk mengetahui peningkatan aktivitas belajar siswa kelas IV SDN 24 Kuala Pade.Penelitian ini menggunakan Penelitian Tindakan Kelas (Classroom Action Research), sebanyak tiga (3) siklus. Setiap siklus terdiri dari empat tahap yaitu: perencanaan tindakan, pelaksanaan tindakan, pengamatan, dan refleksi. Sasaran penelitian ini adalah peserta didik Kelas IV SDN 24 Kuala Pade. Data yang diperoleh lembar observasi kegiatan belajar mengajar dan tes hasil belajar. Perencanaan pembelajaran dengan metode eksperimen pada pembelajaran Ilmu Pengetahuan Alam dikelas IV SDN 24 Kuala Pade telah dilaksanakan kategori Baik Sekali. Hal ini dapat dilihat pada lembar IPKG 1 siklus I dengan Skor rata-rata 3,48, sedangkan IPKG 1 pada siklus II dengan Skor rata-rata 3,72, Dan IPKG 1 pada siklus III dengan Skor rata-rata 3,95.Pelaksanaan pembelajaran dengan metode eksperimen pada pembelajaran Ilmu Pengetahuan Alam di kelas IV SDN 24 Kuala Pade telah dilaksanakan kategori Baik Sekali. Hal ini dapat dilihat pada lembar IPKG 2 pada siklus I dengan Skor rata-rata 3,55, sedangkan IPKG 2 pada II dengan Skor rata-rata 3,93, dan IPKG 2 pada siklus III dengan Skor rata-rata 3,99. Penggunaan metode eksperimen dalam pembelajaran Ilmu Pengetahuan Alam ternyata dapat meningkatkan Aktivitas Belajar peserta didik kelas IV SDN 24 Kuala Pade. Hal ini dapat dilihat pada lembar observasi rata-rata persentase peserta didik untuk aktivitas fisik mulai dari observasi awal (base line) diperoleh 13,88%, pada siklus I diperoleh 71,93%, siklus II diperoleh 83,3% dan siklus III diperoleh 94,43%. Selanjutnya untuk aktivitas mental mulai dari observasi awal (base line) 8,33%, pada siklus I diperoleh 44,29%, siklus II diperoleh 63,86%, dan siklus III diperoleh 83,3%. Dan selanjutnya untuk aktivitas emosional mulai dari observasi awal (base line) 0%, pada siklus I diperoleh 43,16%, siklus II diperoleh 68,98%, dan siklus III diperoleh 83,32%. Dengan demikian penelitian dengan menggunakan metode eksperimen dapat meningkatkan aktivitas belajar peserta didik kelas IV SDN 24 Kuala Pade. Kata Kunci : Metode Eksperimen, Aktivitas Siswa, Hasil Belajar